"I Didn't Tell Anyone Because I Was Very Afraid": Girls' Experiences of Menstruation in Contemporary Ethiopia. Issue 3 (2nd September 2017) - Smiles, Dana; Short, Susan E.; Sommer, Marni
ABSTRACT: Menstrual health is central to girls' well-being and connected to their rights to health, education, safety, nondiscrimination, and autonomy. This article reports an investigation of girls' experiences of menstruation in present-day Ethiopia. Results, based on data collected from 120 girls in two regions, illustrate the challenges associated with menstruation, including menstrual taboos and cultural beliefs about menstruation, myths about menstruation and sex, restrictive social expectations related to marriage, and interpersonal interactions. These challenges diminish girls' health, education, safety, and autonomy and, in so doing, underscore the relevance of menstrual health to human rights agendas that seek to advance girls' well-being.